STUDENTS’ THINKING PROCESS IN SOLVING MATHEMATICS PROBLEMS REVIEWING FROM COGNITIVE STYLE: PROSES BERPIKIR SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI GAYA KOGNITIF - Rahmi Yuliana M.; Hartini (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This research aims to identify and describe the thinking process of students in solving mathematical problems, both students who have a field-independent type of cognitive style (GK-FI) and students who have a field-dependent type of cognitive style (GK-FD). The subjects of this study were eight people, consisting of four GK-FI students and four GK-FD students. Data was collected using the Group Embedded Figure Test (GEFT). The process of selecting subjects was carried out in stages (a) determining the class to be the subject of the study, (b) giving the GEFT test, (c) analyzing the results of the GEFT test, (d) determining the research subjects, each consisting of 4 students. The research process follows the stages: (a) reviewing theory and conducting an initial survey, (b) preparing research instruments, (c) collecting research data both written data and interview data, (d) validating data using triangulation techniques, (e) analyzing data on mathematical problems to get an overview of the procedures used by students in solving mathematical problems, and (f) revealing students' thinking processes in solving mathematical problems based on students' cognitive styles. The thinking processes of GK-FI and GK-FD subjects in solving mathematical problems are as follows: (1) In the process of forming an understanding, the GK-FI subject receives and parses based on its parts, then makes a problem-solving plan, while the GK-FD subject does not parse based on its parts. (2) In the process of forming opinions, the subject of GK-FI performs with an analytical process while the subject of GK-FD performs with a process of trial and error and matching. (3) In the process of drawing conclusions, the GK-FI subject conducts an examination or checks the results first, while the GK-FD subject does not do.